2020
DOI: 10.7547/17-150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Association Between Plantar Fasciitis and Hallux Valgus

Abstract: Background The windlass mechanism, first described by John Hicks in 1954, defines the anatomical and biomechanical relationship between the hallux and the plantar fascia. Hallux valgus (HV) and plantar fasciitis are the most common foot disorders, and, to date, no study has evaluated the relationship between these disorders. The purpose of this study was to determine the incidence of and factors associated with plantar fasciitis in patients with HV deformity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…Although a previous study reported that the incidence of plantar fasciitis increased with the severity of a hallux valgus deformity, 20) the hallux valgus angle and patient-reported symptoms did not show a significant relationship with plantar fasciitis in our patients. The previous study suggested that an abnormal windlass mechanism in hallux valgus deformity could favor the development of plantar fasciitis, 20) but this needs to be validated in biomechanical or cadaveric studies. A flatfoot has been shown to be a causative factor in the development of plantar fasciitis.…”
Section: Discussioncontrasting
confidence: 92%
“…Although a previous study reported that the incidence of plantar fasciitis increased with the severity of a hallux valgus deformity, 20) the hallux valgus angle and patient-reported symptoms did not show a significant relationship with plantar fasciitis in our patients. The previous study suggested that an abnormal windlass mechanism in hallux valgus deformity could favor the development of plantar fasciitis, 20) but this needs to be validated in biomechanical or cadaveric studies. A flatfoot has been shown to be a causative factor in the development of plantar fasciitis.…”
Section: Discussioncontrasting
confidence: 92%
“…Excessive stress in the fascia causes stress damage to the fascia near the attachment of the calcaneus. Continuous repetitive microtrauma is believed to inhibit the normal repair process [15] . By effectively connecting the expansion of the plantar fornix, the plantar fascia is in a state of being stretched during the stress buffering process.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the variations of surgical techniques, the intrinsic features of HV, such as spring ligament insufficiency [ 70 ], first ray hypermobility [ 71 ], hypermobility due to malpractice in amateur ballet dancers [ 72 ], generalized ligament laxity [ 73 ], medial column instability, and posterior tibial tendon dysfunction [ 74 ], may have contributed to clinical heterogeneity as well. Moreover, HV was often compounded with other foot problems that were infeasible to isolate [ 59 , 75 ], such as flatfoot [ 76 ], plantar fasciitis [ 77 ], transfer metatarsalgia [ 18 ], and claw toes [ 78 ]. There is limited research on the impact of plantar pressure under such circumstances.…”
Section: Discussionmentioning
confidence: 99%